Growth rate hypothesis and efficiency of protein synthesis under different sulphate concentrations in two green algae - Giordano, Mario; Palmucci, Matteo; Raven, John A (Plant, cell & environment, 2015)
The growth rate hypothesis (GRH) predicts a positive correlation between growth rate and RNA content because growth depends upon the protein synthesis machinery. The application of this hypothesis to photoautotrophic organisms has been questioned. We tested the GRH on one prasinophycean, Tetraselmis suecica, and one chlorophycean, Dunaliella salina, grown at three sulphate concentrations. Sulphate was chosen because its concentration in the oceans increased through geological time and apparently had a role in the evolutionary trajectories of phytoplankton. Cell protein content and P quota were positively related to the RNA content (r = 0.62 and r = 0.74, respectively). The correlation of the RNA content with growth rates (r = 0.95) indicates that the GRH was valid for these species when growth rates were below 0.82 d(-1) .
Keywords: Oceans and Seas; sírany; phosphorus; sulphate; growth; proteosyntéza; Sulfates; Chlorophyta; oceány a moře; mořská voda; RNA; dusík; Nitrogen; Protein Biosynthesis; Seawater; Ribosomes; ribozomy